10 steps to creating an infographic a practical guide for non- designers - Wilkerson, Stephanie B. (Thousand Oaks, California Sage, 2024)
"This book provides step-by-step guidance for developing high-quality infographics. Practical in its approach, 10 Steps to Creating an Infographic: A Practical Guide for Non-designers outlines a user-friendly process for developing infographics with a clearly defined purpose and powerful message. The book’s “how-to” approach makes infographic creation accessible for anyone who doesn’t have a background in graphic design or a budget for a graphic designer."
Step 1: Identify your audience (the "who") -- Step 2: Clarify the purpose (the "why") -- Step 3: Create the story (the "what") -- Step 4: Identify data and visuals -- Step 5: Select a layout -- Step 6: Choose design elements -- Step 7: Sketch your ideas -- Step 8: Draft the infographic -- Step 9: Review the infographic -- Step 10: Revise, finalize, and share.
Includes bibliographical references (pages 171-177) and index.
Keywords: Visual communication; Communication -- Graphic methods